2011
DOI: 10.3122/jabfm.2011.03.100212
|View full text |Cite
|
Sign up to set email alerts
|

Time, Costs, and Clinical Utilization of Screening for Health Literacy: A Case Study Using the Newest Vital Sign (NVS) Instrument

Abstract: Limited health literacy, defined broadly as the diminished capacity to obtain, understand, and act on basic health-related information, has been identified as an important factor impacting the quality of health care today.1-4 More specifically, limited health literacy has been identified as a risk factor for a number of adverse outcomes, including the underuse of preventive services, limited patient participation in medical decision making, poor selfmanagement/reduced adherence, delayed presentation and diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…Previous studies [12][13][14][15][16] examining associations between healthcare utilization, expenditures and health literacy were limited to individual-level interpretations given their measurement approaches. [12][13][14][15][16] To address this shortcoming, we conducted the current study, which is multilevel (eg, a Predicted expenditure and number of visits are adjusted for person's type of insurance coverage and region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies [12][13][14][15][16] examining associations between healthcare utilization, expenditures and health literacy were limited to individual-level interpretations given their measurement approaches. [12][13][14][15][16] To address this shortcoming, we conducted the current study, which is multilevel (eg, a Predicted expenditure and number of visits are adjusted for person's type of insurance coverage and region.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] To address this shortcoming, we conducted the current study, which is multilevel (eg, a Predicted expenditure and number of visits are adjusted for person's type of insurance coverage and region. Visits are modeled with non-negative binomial regression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 These researchers, however, used the NVS as a self-administered tool, which was not how the instrument was developed, and validated. The researchers concluded that while primary care practitioners were willing to employ new communication strategies based on fi nding of the NVS, the practitioners tended to revert to usual practice quite rapidly, thus abandoning the information provided by the NVS.…”
Section: Clinical Usementioning
confidence: 99%
“…In one office, 11 an attempt to implement a health literacy instrument was not particularly sustainable, probably at least partly because its value in the clinical setting was elusive. Bluestein 12 looked at factors associated with the acceptance of behavioral treatments for insomnia.…”
Section: Health Literacy Screening Of Unclear Practical Helpmentioning
confidence: 99%